Spectrophotometric Estimation of Nitrazepam in Pure and in Pharmaceutical Preparations - Hemavathi Nagaraju Deepakumari; Hosakere Doddarevanna Revanasiddappa (Journal of Spectroscopy)
Three simple, sensitive, accurate, and rapid visible spectrophotometric methods (A, B, and C) have been developed for the estimation of nitrazepam in both pure and in pharmaceutical preparations. They are based on the diazotization of reduced nitrazepam with nitrous acid followed by coupling with acetyl acetone (method A), diphenylamine (method B), and citrazinic acid (method C) to form colored azo-dyes, exhibiting absorption maxima () at 400, 550, and 460 nm, for methods A, B, and C, respectively. The produced colored azo-dyes are stable for more than 2 h. Beer's law was obeyed in the concentration range of 0.5–20, 0.3–14 and 0.5–12 μg/mL for methods A, B, and C, respectively and the corresponding molar absorptivity values are , , and  L mol−1cm−1. All variables have been optimized and the results were statistically compared with those of a literature method by employing the Student's t-test and F-test. No interference was observed from common adjuvants normally added to the tablets. The results obtained in the proposed methods are in good agreement with labeled amounts, when marketed pharmaceutical preparations are analyzed, which could be applied in the routine quality control analysis laboratory.